Analysis of Factors Affecting the Behaviour of Medical Personnel in Carrying Out Hand Hygiene - Dwi Mitra Sari; Didik Dwi Winarno (Universitas Airlangga, 2022)
Introduction: The activities of health workers in carrying out their profession are very risky for nosocomial infections and very high infectious diseases . The Ministry of Health urges every medical personnel to carry out hand hygiene as an effort to minimize the occurrence of nosocomial infections. The purpose of this study was to determine the factors which affect the behaviour of medical personnel in carrying out hand hygiene protocols. Methods: This research was a correlational descriptive research. The population in this study were medical personnel of Kebonsari Public Health Center Surabaya, and the samples were taken using a simple random sampling technique with a total of 63 respondents. The variables in this study were knowledge, attitude, training, commitment, supervision and behaviour. Data collection was carried out using a questionnaire sheet, direct observation and statistical test using a path analysis. Results: The results of simultaneous statistical tests upon knowledge, attitude, training, commitment, and supervision showed that those 5 factors had an effect on hand hygiene behaviour with 45.6% coefficient of determination (R2), and the results of a partial statistical test (t test) on knowledge, training, commitment, and supervision showed a significant effect on hand hygiene behavior of < 0.05, while attitudes had no significant effect on hand hygiene behavior of > 0.05. Conclusion: Knowledge, training, commitment and supervision affected the behaviour of medical personnel in carrying out hand hygiene. These variables, theoretically, contribute to forming good behaviour.Keywords: behavioral factors, hand hygiene, medical personnel